ANALISA KEKUATAN KONSTRUKSI PADA DESAIN RAMP DOOR KAPAL JENIS MULTIPURPOSE - Tristiandinda Permata; Aurista Miftahatul Ilmah (EINSTEIN (e-Journal), 2023)
Ferry ships generally have various kinds of cargo such as passengers, motorbikes, livestock, or goods carried by passengers. The process of transferring the load requires a special path or path in its transfer which is called a Ramp door. One of the important factors in making Ramp doors is their strength, so there is a need for strength analysis in rampdoor design on certain types of ships, one of which is multipurpose ships, strength analysis on ramp doors for certain loads can be visualized using solidwork software.In a comparison of the strength analysis between using the software and calculating the stress, the difference is not that significant and the biggest difference is the calculation of the stress on the load of passengers riding motorbikes when going through the Ramp door. From the results obtained in the calculations and the software, there is a difference of 4.29 % with the safety factor in accordance with the rules of safety factor, which exceeds the number 1.